Effect of Amphotericin B on Growth and Membrane Permeability in Dictyostelium discoideum - Rossomando, Edward F. (1976)
In this study we have determined the effect of the polyene antibiotic amphotericin B on the growth of the eukaryotic microorganism Dictyostelium discoideum. These experiments show that the addition of drug to axenically growing cultures results in an inhibition of growth and cell division. However, with continued incubation, growth is resumed. To determine if the inhibitory effect was due to cell death, the effect of the drug on cell viability was measured. The results showed 10 to 20 times more drug was required to kill cells than to inhibit growth. Since previous studies had indicated that drugs of this type modified cellular permeability, the effect of this drug on osmotic stability of these cells was determined. Results reported in this study show that amphotericin B treatment modifies the cell surface, producing osmotically unstable cells, and that this modification occurs before the onset of cell death and within the same concentration range as used to bring about the inhibition of growth and division. Based on these data it is suggested that the modification in cellular permeability produced by the drug results in the inhibition of growth. This study also reports the results of experiments on the fate of the membrane-damaged cells. These experiments, using radioactive thiourea, showed the restoration of cellular permeability barrier and suggested that the resumption of cell growth occurs after the completion of the repair process.